Tandem fluorescent protein timers for in vivo analysis of protein dynamics - Khmelinskii, Anton; Bartosik, Anna; Meurer, Matthias; Mardin, Balca; Pereira, Gislene; Huber, Wolfgang; Schiebel, Elmar; Knop, Michael (Nature biotechnology, 2012)
The functional state of a cell is largely determined by the spatiotemporal organization of its proteome. Technologies exist for measuring particular aspects of protein turnover and localization, but comprehensive analysis of protein dynamics across different scales is possible only by combining several methods. Here we describe tandem fluorescent protein timers (tFTs), fusions of two single-color fluorescent proteins that mature with different kinetics, which we use to analyze protein turnover and mobility in living cells. We fuse tFTs to proteins in yeast to study the longevity, segregation and inheritance of cellular components and the mobility of proteins between subcellular compartments; to measure protein degradation kinetics without the need for time-course measurements; and to conduct high-throughput screens for regulators of protein turnover. Our experiments reveal the stable nature and asymmetric inheritance of nuclear pore complexes and identify regulators of N-end rule-mediated protein degradation.